A PURIFICATION AND CHARACTERIZATION OF HIGH MOLECULAR WEIGHT HEMORRHAGIN PRESENT IN THE SNAKE VENOM Bothrops pictus - Bellido, Candy (2016)
A hemorrhagin with metalloprotease activity was purified from the venom of Bothrops pictussnake using Sephadex G-75 molecular gel filtration and DEAE A-50 ionic exchange column.Thus a homogeneus protein entity was obtained with 62 kDa under non reducting conditions.Hemorrhagin is a acid protein, attack both casein and collagen being 0,226 μg as a DHM.Chelating agent such as EDTA as well as 2 ß-mercaptoetanol and DTT produced stronginhibition both caseinolitic and hemorrhagic activities. Optimus pH was 7,5 and heatingtreatment reduced both activities, At 55 °C recovered activity on casein was 30,4%. On theother hand hemorrhagin is an antigenic entity showed on double immunodiffusion test andwas neutralizated fulling with 0,5, 1 and 2 doses of antivenom.